Analysis of the Influence of Health Education Through Social Media on Students' Hand Washing Behavior - Meilinda, Vivi; Sumiyati, Sumiyati (Indonesian Health Journal, 2025)
Handwashing behavior is a key pillar in preventing infectious diseases, but awareness and consistency were still low among students before the COVID-19 pandemic. In the digital era, social media has become a potential channel for delivering health education massively and interactively. This study aims to analyze the effect of health education exposure through social media on handwashing behavior in students and identify the relationship between knowledge levels and hygienic practices. This study used a quantitative approach with a cross-sectional analytical survey design . A sample of 385 students was selected stratified. random sampling. The research instrument was a structured online questionnaire that included variables of educational exposure, knowledge, and handwashing behavior. Data were analyzed using Pearson correlation and simple linear regression. The results showed a very strong and significant relationship between exposure to health education through social media and handwashing behavior (r = 0.995; p < 0.01). The linear regression model produced R² = 0.991, which means that educational exposure explains 99.1% of the variation in handwashing behavior. Visual platforms such as TikTok and Instagram have proven to be more effective than text-based media. This study demonstrates the importance of utilizing social media as a strategic tool in preventive health promotion among college students and encourages the design of more targeted and evidence-based digital interventions.